Lung Function and Respiratory Symptoms Features of Smoker among University Students - Nathaniel Jason Zacharia; Triya Damayanti; Adityo Wibowo (Jurnal Respirasi, 2022)
Introduction: Smoking habit still becomes one of the problems in Indonesia with the high number of active smokers in university students. Smoking is one of the causes of several conditions of respiratory symptoms and risk factor of multiple case of lung function impairment. This study aimed to examine characteristic of lung function and respiratory symptoms and its relationship in active smokers among university student in Depok, Indonesia. Methods: This was a cross-sectional study using American Thoracic Society (ATS) questionnaire for respiratory symptoms and Brinkman index for smoking habits. Lung function was examined using EasyOne® Air Spirometer. Results: This study was participated by 116 male university students who are active smokers. This study found that majority of respondents fell into the mild category of smoking habit (96.56%) and complained of respiratory symptoms (74.14%). This study found lung function impairment in 15.5% respondents (8.6% obstructive and 6.9% restrictive disorder). There was no significant relationship between smoking habits with respiratory symptoms and lung function impairment among respondents. Conclusion: This study found the characteristics of smoking habits in male university students were categorized as mild smoking habit, followed by the appearance of respiratory symptoms and lung function impairment. However, there was no significant relationship between smoking habits and respiratory symptoms or lung function. This issue needs to be paid attention to strengthen the campaign to prevent smoking initiation and to help smoking cessation among young adults as early as possible.